Medical care for children with activity and attention disorders - Bartašiūnienė, Vida; Petravičienė, Zita (Slauga. Mokslas ir praktika, 2021)
Impulsiveness, inattention and high activity are the hallmarks of children. Many consider these traits to be normal behavior in children; unfortunately, sometimes the severity of these traits reaches a degree of disorder when the help of competent professionals is required. The aim of the study was to analyze the medical care of children with activity and attention disorders. A qualitative study was performed. The research tool is a semi-structured interview. The study involved 6 nurses working at the Child Development Center and 6 visiting parents of children. The study showed that children with activity and attention disorders are impulsive, distracted, intrusive, restless, and cause a lot of trouble not only for their parents but also for professionals. Prolonged disorders require complex treatment, nursing and care. Specialists control children's impulsivity, communicate with the child and his parents, find out the need for help, analyze the child's mental health. The most common mental problems in children and adolescents are activity and attention disorders.
Keywords: nursing; specialist; nurse; child's mental health